2015
DOI: 10.1073/pnas.1518384112
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of household food availability in sub-Saharan Africa based on big data from small farms

Abstract: We calculated a simple indicator of food availability using data from 93 sites in 17 countries across contrasted agroecologies in subSaharan Africa (>13,000 farm households) and analyzed the drivers of variations in food availability. Crop production was the major source of energy, contributing 60% of food availability. The off-farm income contribution to food availability ranged from 12% for households without enough food available (18% of the total sample) to 27% for the 58% of households with sufficient foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
284
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 315 publications
(318 citation statements)
references
References 30 publications
30
284
3
1
Order By: Relevance
“…This food availability indicator closely correlates to well-established indicators such as the Household Dietary Diversity Score (HDDS) and the Household Food Insecurity Access Scale (HFIAS) (Hammond et al 2016). Frelat et al (2016) observed that household food availability improved with increasing dependency on off-farm activities, suggesting diverse strategies among rural households. Frelat et al (2016) analysed cross-sectional household data from more than 13,000 households across 97 locations in 17 countries across sub-Saharan Africa (SSA), yet their spatial coverage across the continent in general and Uganda in particular was poor; e.g.…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…This food availability indicator closely correlates to well-established indicators such as the Household Dietary Diversity Score (HDDS) and the Household Food Insecurity Access Scale (HFIAS) (Hammond et al 2016). Frelat et al (2016) observed that household food availability improved with increasing dependency on off-farm activities, suggesting diverse strategies among rural households. Frelat et al (2016) analysed cross-sectional household data from more than 13,000 households across 97 locations in 17 countries across sub-Saharan Africa (SSA), yet their spatial coverage across the continent in general and Uganda in particular was poor; e.g.…”
Section: Introductionmentioning
confidence: 59%
“…For each household a simple food availability (FA) indicator was calculated following Frelat et al (2016). The FA indicator (FA) estimates the average amount of potential food energy that is available to each male adult household member equivalent per day [kcal cap…”
Section: Household Level Food Availabilitymentioning
confidence: 99%
See 3 more Smart Citations